Qur'anization of Rural Communities: A Living Qur'an Study of Rural Muslim Communities - aziza nadiya; libasut taqwa (UIN Kiai Haji Achmad Siddiq Jember, 2026)
This study examines the process of “Qur’anization” in rural communities through the study of the Living Qur’an, which refers to the implementation of Qur’anic values into the social life of the community through religious activities rooted in tradition. The research method used is qualitative with a Living Qur’an approach. Data was obtained through participatory observation, in-depth interviews with religious leaders and congregations, and documentation of activities. The results of the study show that there are four main forms of Qur’anization practices, including: First, the activity of reciting the Qur’an, which serves as a means to strengthen the ability to read the Qur’an and as a medium for passing on Islamic values from one generation to the next. Second, Rabu Wekasan as a means of warding off evil spirits. Third, Lailatul Ijtima’ as a means of conveying religious knowledge and Islamic values. Fourth, the Megengan tradition as a form of gratitude and friendship. These four practices show that Qur’anization at the Muslim Community of Baitus Salam is not merely a ritual activity, but a form of religious transformation that bridges the teachings of the Qur’an and the social life of the village community. Keywords: Qur’anization, Living Qur’an, Rural Commmunity